Pengaruh Dukungan Sosial Pada Penderita Sistemik Lupus Eritematosus (SLE): Literature Review - Linggar Catur Nursiwi; Abdul Aziz; Iswanti Purwaningsih (SAMODRA ILMU: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2022)
Background: The high prevalence of lupus in Indonesia is of particular importance to the community in terms of raising awareness of the illness. The condition of the body's organs may be impacted by the requirement for social support and self-confidence in order to improve health status. The social support that can be provided takes the shape of consideration and comfort. To ascertain how patients with Sistemik Lupus Eritematosus (SLE). Method: Using a library or literature review as a method. The type of analysis used in this study is descriptive, which is a systematic breakdown of the collected data. The information used in this study is secondary data, namely information that was sampled and evaluated from five different research publications. Search for journals using Google Scholar, BASE and PNRI. Results: a value with an average of p = 0.000 (p 0.05) was found from all of the examined articles. Consequently, it can be said that Ho is rejected and Ha is accepted because the results of the hypothesis reached a significant value. Conclusion: Patients with Systemic Lupus Erythematosus benefit from social support (SLE). Implication: Incorporating research into nursing care for SLE patients, offering social support, and boosting their self-confidence are all possible.